Relation Entre Le Somatotype Et La Qualite De Vitesse Chez Des Jeunes De Cote d’Ivoire - Coulibaly, Siaka; Kouamé, N’guessan; Kouassi, Firmin Kouakou; Kouadio, Jérôme Kouakou; Beugré, Jean-Bertin; Pineau, Jean-Claude (European Scientific Journal, ESJ, 2016)
The aim of this study is to establish a link between the performance at speed race and the somatotype within young students from Côte d’Ivoire who are candidates for the recruitment test organized by the National Institute of Youth and Sports. The study was performed on 669 girls at 21.80+2.26 year old and 1859 boys at 22.11+2.26 years. Anthropometrical measures were made out in order to estimate somatotype. For the speed, the subjects underwent a 80m speed race test for girls and a 100m speed race for boys. After a descriptive analysis of the somatotype components and the performance of girls and boys, we made a distribution of the gaps in performance (estimated performance – real performance) estimated by the regression and the real performance in order to check normality. To examine the relationship between somatotype, cormic index and the speed race, an equation of multiple regressions was performed. The distribution of the gaps in performance (estimated performance - real performance) estimated by the regression and real performance is normally distributed both in girls and boys. The results also indicate that a multiple and statistically significant link (p<0.05) exists between the performance and three (3) variables: endormorphy, ectomorphy and cormic index with boys and two (2) components of somatotype: endomorphy, mesomorphy with girls. The present study has allowed establishing a relationship between the performance at speed race and some of the components of the somatotype. The performance at 100m for boys and 80m for girls is well the result of a specific morphotype (endomorph) limiting the realization of good performances by these sprinters.